A retinoic acid receptor β2 agonist protects against alcohol liver disease and modulates hepatic expression of canonical retinoid metabolism genes. (22nd October 2021) - Melis, Marta; Tang, Xiao‐Han; Attarwala, Nabeel; Chen, Qiuying; Prishker, Carlos; Qin, Lihui; Gross, Steven S.; Gudas, Lorraine J.; Trasino, Steven E.
Abstract: Alcohol abuse reduces hepatic vitamin A (retinoids), reductions that are associated with progression of alcohol liver disease (ALD). Restoring hepatic retinoids through diet is contraindicated in ALD due to the negative effects of alcohol on retinoid metabolism. There are currently no drugs that can both mitigate alcohol‐driven hepatic retinoid losses and progression of ALD. Using a mouse model of alcohol intake, we examined if an agonist for the retinoic acid (RA) receptor β2 (RARβ2), AC261066 (AC261) could prevent alcohol‐driven hepatic retinoid losses and protect against ALD. Our results show that mice co‐treated with AC261 and alcohol displayed mitigation of ALD, including reduced macro, and microvesicular steatosis, and liver damage. Alcohol intake led to increases in hepatic centrilobular levels of ALDH1A1, a rate‐limiting enzyme in RA synthesis, and co‐localization of ALDH1A1 with the alcohol‐metabolizing enzyme CYP2E1, and 4‐HNE, a marker of oxidative stress; expression of these targets was abrogated in mice co‐treated with AC261 and alcohol. By RNA sequencing technology, we found that AC261 treatments opposed alcohol modulation of 68 transcripts involved in canonical retinoid metabolism. Alcohol modulation of these transcripts, including CES1D, CES1G, RBP1, RDH10, and CYP26A1, collectively favor hepatic retinoid hydrolysis and catabolism. However, despite this, co‐administration of AC261 with alcohol did not mitigate alcohol‐mediated depletions of hepatic retinoids, but did reduce alcohol‐driven increases in serum retinol. Our data show that AC261 protected mice against ALD, even though AC261 did not prevent alcohol‐mediated reductions in hepatic retinoids. These data warrant further studies of the anti‐ALD properties of AC261.